Physicochemical constraints and fluid evolution pathways in skarn mineralization: insights from sphalerite geochemistry at the Dafang Pb–Zn–Au–Ag deposit, South China - Wang, Wusheng; Shen, Hongjie; Huang, Shihong; Shi, Jian; Zhang, Yu (Frontiers in Earth Science, 2025)
Important Mid-Late Jurassic Pb–Zn polymetallic skarn deposits are widely distributed in South China, yet physiochemical conditions and migration of the ore-forming fluids in skarn deposits are poorly constrained. The Dafang Pb–Zn–Au–Ag deposit (38 kt Pb @ 1.4%, 33 kt Zn @ 1.3%, 6.1 t Au @ 1.80 g/t, and 370 t Ag @ 106.8 g/t) represents a typical skarn deposit in the South Hunan district, located at the intersection between the Nanling Region and the Qin-Hang Metallogenic Belt in South China. Its mineralization can be divided into four stages: (I) prograde skarn, (II) retrograde alteration, (III) quartz-sulfides, and (IV) carbonate-sulfides stages. Within the Dafang deposit, the primary Pb–Zn mineralization is prominently occurred in the principal calcite-sulfides stage (Stage IV). Within this stage, sphalerite exhibits distinct spatial distribution characteristics across three orebody types, allowing for its systematic classification into Sp-I (Orebody I), Sp-II (Orebody II), and Sp-III (Orebody III). This study investigates the textural characteristics and trace element geochemistry of these three sphalerite types to unravel the physicochemical conditions of mineralization and fluid pathways. Backscattered electron (BSE) imaging reveals that Sp-I, Sp-II, and Sp-III all display homogeneous internal textures and appear grayish-black. Detailed textural observations indicate that Sp-I is primarily associated with galena but is subsequently replaced by arsenopyrite, pyrite, and calcite. Sp-II is typically replaced by arsenopyrite and pyrite and hosts minor inclusions of chalcopyrite and stannite. Both Sp-III and coexisting galena are overprinted by pyrite, arsenopyrite, and calcite. Trace element analyses demonstrate two primary incorporation mechanisms within Dafang sphalerite: divalent cations (e.g., Fe2+, Cd2+, and Mn2+) substitute directly for Zn2+ through isovalent substitution, while trivalent and tetravalent cations (e.g., Sb3+, Ga3+, In3+, and Ge4+) incorporate via charge-coupled substitution involving Cu+ and/or Ag+ to maintain electrostatic equilibrium. Crucially, the trace element geochemistry of Dafang sphalerite reveals a progressive decrease in temperature and sulfur fugacity from Sp-III (∼285 °C; lg fS2 = −8.1 to −10.4, avg. −9.0) to Sp-II (∼280 °C; lg fS2 = −9.8 to −8.7, avg. −9.1) and subsequently to Sp-I (∼279 °C; lg fS2 = −9.5 to −9.3, avg. −9.4). This systematic variation in physicochemical conditions, particularly the spatially decreasing temperature gradient from NW to SE as indicated by the SPRFT geothermometer, suggests that ore-forming fluids migrated from the Lashuxia pluton towards the Maoerling pluton. This finding identifies the Lashuxia pluton as the primary metallogenic source, offering critical insights for the favorable target area for future exploration within the Dafang Pb–Zn–Au–Ag deposit.